(untitled) (Bangladesh Journal of Plant Taxonomy, 2018)
Colocasia hassanii, a new species of Araceae from Bangladesh, is described and illustrated. C. hassanii is closely related to C. esculenta (L.) Schott but differs from the later by the number of constriction (two) in spathe, presence of a sterile male zone in spadix, and bitter in taste. A morphological comparison between C. hassanii and C. esculenta is provided. Bangladesh J. Plant Taxon. 25(1): 101-106, 2018 (June)